Transmission Routes of Severe Acute Respiratory Syndrome Coronavirus 2 Among Healthcare Workers of a French University Hospital in Paris, France. (2nd February 2021) - Contejean, Adrien; Leporrier, Jérémie; Canouï, Etienne; Fourgeaud, Jacques; Mariaggi, Alice-Andrée; Alby-Laurent, Fanny; Lafont, Emmanuel; Beaudeau, Lauren; Rouzaud, Claire; Lecieux, Fabienne; Greffet, Agnès; L'Honneur, Anne-Sophie; et al.
Abstract: In this case-control study on 564 healthcare workers of a university hospital in Paris (France), contacts without protection with coronavirus disease 2019 (COVID-19) patients or with colleagues were associated with infection with severe acute respiratory syndrome coronavirus 2, whereas working in a COVID-dedicated unit and having children kept in childcare facilities were not.